Yersiniosis with a predominance of articular syndrome: challenges of outpatient admission. Clinical case - Alexander A. Kopelev; Margarita A. Gromova; Julia B. Chervyakova (LLC "MEDIAFORMAT", 2021)
The articular syndrome, although it requires, first of all, the exclusion of systemic diseases of the connective tissue, contrary to the common stereotype, is rather nonspecific. It can also be accompanied by infectious pathology, the incidence of various variants of which is quite high. On an outpatient basis, doctors of any specialty are faced with yersiniosis, the clinical manifestations of which are polymorphic and similar to those of other diseases. Below is an example of the course of yersiniosis with a predominance of articular syndrome in the clinical picture.